Neuropathic pain in multiple sclerosis: serum biomarkers and MRI lesion localization - Mohamed Hamdy Ismail; Amal SE ELmotayam; Sara F. Saadawy; Rabab M. Elfwakhry; Hebatallah M. Fawzy; Noha T. Sarhan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Multiple sclerosis (MS) is a chronic disease characterized by loss of central myelin, leading to various neurological impairments and frequently affecting the quality of life. A significant factor influencing the quality of life is pain, which is a personal experience and lacks a precise mathematical or manual method of quantification. Several varying factors, such as the patient's current psychological state, cognitive abilities, and environment can affect these measurements. This study aims at evaluating potential serological biomarkers of neuropathic pain in multiple sclerosis patients and correlating neuropathic pain with localization of lesions and burden of disease attributed to this symptom. This research builds upon preliminary findings presented as a poster at the 9th MENACTRIMS congress in 2024 by Sarhan et al. (Mult Scler Relat Disord 92:106003, 2024). Results This cross-sectional study was conducted on 64 clinically definite Relapsing Remitting MS patients based on MacDonald’s criteria selected from the Zagazig University MS Outpatient Clinic. Among these patients, 40.6% reported experiencing pain as measured by The Leeds Assessment of Neuropathic Symptoms and Signs scale, while the visual analog scale indicated that 23.4 and 18.8% experienced moderate and severe pain, respectively. Interleukin-6 (IL6), Interleukin-10 (IL10), and tumor necrosis factor (TNF) levels were evaluated in our patients, revealing that these serological markers were significantly elevated in those suffering from severe and moderate pain (p < 0.001) across all applied pain assessment tools. The incidence of pain was notably higher in patients who had thalamic, brainstem, and spinal cord lesions as observed through magnetic resonance imaging (MRI). Conclusion Neuropathic pain was highly prevalent in multiple sclerosis, Serum IL-6, IL-10 and TNF were associated with pain severity, also MRI lesion localization appeared to have association with neuropathic pain in MS, further research is warranted for more understanding of the pathophysiology of pain in multiple sclerosis and identifying the underlying biomarkers which may aid as a therapeutic target and help improving quality of life.